COLLABORATIVE MANAGEMENT OF INDRAYANTI BEACH ECO-TOURISM BASED ON LOCAL WISDOM IN SIDOHARJO TEPUS VILLAGE, GUNUNGKIDUL YOGYAKARTA - Bernadus Sumarwoto; Agus Subianto; Ninis Trisyani (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2021)
The purpose of this research is to describe collaborative efforts in the management of coastal tourism and to describe the supporting and inhibiting factors in the collaborative management of ecotourism-based Indrayanti coastal tourism. This type of research is descriptive qualitative. The research location is Indrayanti Beach, Gunungkidul Regency. The research informants used purposive sampling, namely the Tourism Office of the Gunung Kidul Regency Government, the Head of Sidoharjo Village, the private sector, academics, and the Sidoharjo Village Community. Collecting data used interviews, documentation, and observation. The data analysis technique uses qualitative. The results of the study show that the collaborative management of ecotourism-based Indrayanti coastal tourism has been going well. The Regency Government and Village Government support with facilities and infrastructure. The private sector plays a role in the establishment of lodging, restaurants, and souvenir shops, the community plays a role in beach management starting from cleanliness, also establishing souvenir shops, academics play a role in research development, while the existence of the media is carried out through online media to introduce ecotourism on Indrayanti Beach. Supporting factors for collaborative tourism management based on local wisdom of Indrayanti beach in Sidoharjo Tepus Village, Gunungkidul Yogyakarta, among others are natural charm, facilities and infrastructure, and access, while the inhibiting factor is the limited ability of the local community. Keywords: Collaboration, beach tourism, ecotourism, local wisdom.